Noise and vibration hazard in Poland (synthesis of a report) - ENGEL, Zbigniew; SADOWSKI, Jerzy (Archives of Acoustics, 1985)
This elaboration is a synthesis of the report "Noise and vibration hazard in Poland", prepared by a research group appointed by the Committee on Acoustics of the Polish Academy of Sciences, including Prof. Z. ENGEL (Chairman), Prof. L. GRZEGORCZYK, R. KUCHARSKI, M. Sc., Ass. Prof. A. LlPOWCZAN. Ass. Prof. Cz. PUZYNA, Prof. J. SADOWSKI, Ass. Prof. W.SUŁKOWSKI, with the cooperation of a broad group of experts. The report includes complex information on the noise and vibration hazard in Poland and on all the activities performed here to decrease the level of vibration and noise in the environment of man.